Climate Driven Changes in Timing, Composition and Magnitude of the Baltic Sea Phytoplankton Spring Bloom - Hjerne, Olle; Hajdu, Susanna; Larsson, Ulf; Downing, Andrea S.; Winder, Monika (Frontiers in Marine Science, 2019)
Spring phytoplankton blooms contribute a substantial part to annual production, support pelagic and benthic secondary production and influence biogeochemical cycles in many temperate aquatic systems. Understanding environmental effects on spring bloom dynamics is important for predicting future climate responses and for managing aquatic systems. We analyzed long-term phytoplankton data from one coastal and one offshore station in the Baltic Sea to uncover trends in timing, composition and size of the spring bloom and its correlations to environmental variables. There was a general trend of earlier phytoplankton blooms by 1-2 weeks over the last 20 years, associated with more sunshine and less windy conditions. High water temperatures were associated with earlier blooms of diatoms and dinoflagellates that dominate the spring bloom, and decreased diatom bloom magnitude. Overall bloom timing, however, was buffered by a temperature and ice related shift in composition from early blooming diatoms to later blooming dinoflagellates and the autotrophic ciliate Mesodinium rubrum. Such counteracting responses to climate change highlight the importance of both general and taxon-specific investigations. We hypothesize that the predicted earlier blooms of diatoms and dinoflagellates as a response to the expected temperature increase in the Baltic Sea might also be counteracted by more clouds and stronger winds. A shift from early blooming and fast sedimenting diatoms to later blooming groups of dinoflagellates and M. rubrum at higher temperatures during the spring period is expected to increase energy transfers to pelagic secondary production and decrease spring bloom inputs to the benthic system, resulting in lower benthic production and reduced oxygen consumption.